Effect of age and abomasal puncture on peritoneal fluid, hematology, and serum biochemical analyses in young calves - Mendes, Luiz Claudio N. [UNESP]; Peiró, Juliana R. [UNESP]; Feitosa, Francisco Leydson F. [UNESP]; Luvizotto, Maria Cecilia R. [UNESP]; Borges, Alexandre S. [UNESP]; Ciarlini, Paulo César [UNESP]; Venturoli Perri, Sílvia Helena [UNESP] (My University, 2005)
The goals of this study were to evaluate techniques for collection of peritoneal fluid from calves, establish reference ranges for fibrinogen in peritoneal fluid during the 1st month of life, and determine if abomasal puncture would alter peritoneal fluid or hematologic variables. Twenty-two healthy Holstein calves underwent 3 peritoneal fluid collections on day 1, day 15, and day 30 of age. Fibrinogen concentration in peritoneal fluid was 0.20 g/dL and 0.10 g/dL (P < .05) for day 1 and day 30, respectively, and 0.10 at day 15 (P > .05) for calves without abomasal puncture. Plasma fibrinogen concentration was 0.60 g/dL and 0.70 g/ dL (P < .05) for days 15 and 30, respectively, in calves without abomasal puncture. There were no significant differences (P ≤ .05) in peritoneal fluid and peripheral blood total protein and fibrinogen concentrations, specific gravity, total and differential cell count, or erythrocyte counts between calves with or without abomasal puncture. We concluded that the reference ranges established for fibrinogen and total protein concentration are important for accurate evaluation of peritoneal fluid in calves for further comparison with similar-aged animals with gastrointestinal-tract or abdominal-cavity disease. Additionally, accidental abomasal puncture does not alter values of fibrinogen, total protein, and nucleated cell count in peritoneal fluid and does not cause apparent clinical abnormalities. Copyright © 2005 by the American College of Veterinary Internal Medicine.
Keywords: Abdominal paracentesis; Bovine; Fibrinogen; Total protein